Contemporary abstract algebra - Gallian, Joseph A. (Houghton Mifflin, 2006)
Contemporary Abstract Algebra, Sixth Edition, by Joseph A. Gallian includes challenging topics in abstract algebra and many new exercises. The updated biographies, computer exercises, and suggested readings give the text a current and interesting feel. Student resources are available on the text-specific student website. Instructor resources are available on the text-specific, password-protected instructor website. Please refer to the preface of this book for full descriptions of the supplemental print and electronic resources.